2014
DOI: 10.1155/2014/294150
|View full text |Cite
|
Sign up to set email alerts
|

BMP-2 Overexpression Augments Vascular Smooth Muscle Cell Motility by Upregulating Myosin Va via Erk Signaling

Abstract: Background. The disruption of physiologic vascular smooth muscle cell (VSMC) migration initiates atherosclerosis development. The biochemical mechanisms leading to dysfunctional VSMC motility remain unknown. Recently, cytokine BMP-2 has been implicated in various vascular physiologic and pathologic processes. However, whether BMP-2 has any effect upon VSMC motility, or by what manner, has never been investigated. Methods. VSMCs were adenovirally transfected to genetically overexpress BMP-2. VSMC motility was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…These interesting results show Erk1/2 as a regulatory factor in the cardiac induction process. In this sense, previous authors have proposed a similar active role of Bmp in the regulation of FGF/ERK pathway at later stages of cardiovascular development, i.e., during cardiomyocyte differentiation of the anterior heart field (Tirosh-Finkel et al, 2010;Hutson et al, 2010), and during modulation of myosin in vascular smooth muscle cells (Zhang et al, 2014). Taking into account all the above data, we have analyzed the possible influence of some additional factors in order to establish a mechanism which justifies a control pathway of FGF/MAPK from Bmp2 during early cardiac specification.…”
Section: Mir130 Regulates Negative Fgf8-bmp2 Feed-backmentioning
confidence: 69%
“…These interesting results show Erk1/2 as a regulatory factor in the cardiac induction process. In this sense, previous authors have proposed a similar active role of Bmp in the regulation of FGF/ERK pathway at later stages of cardiovascular development, i.e., during cardiomyocyte differentiation of the anterior heart field (Tirosh-Finkel et al, 2010;Hutson et al, 2010), and during modulation of myosin in vascular smooth muscle cells (Zhang et al, 2014). Taking into account all the above data, we have analyzed the possible influence of some additional factors in order to establish a mechanism which justifies a control pathway of FGF/MAPK from Bmp2 during early cardiac specification.…”
Section: Mir130 Regulates Negative Fgf8-bmp2 Feed-backmentioning
confidence: 69%
“…VSMCs represent a significant source of BMP-2, which has been reported to be highly expressed in human vessels [ 34 , 35 ]. Moreover, several studies have consistently shown that BMP-2 enhances VSMC migration [ 36 , 37 ]. Hyperglycemia plays a key role in the regulation of the vascular inflammatory response by activating the recruitment of inflammatory cells to injured arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Although BMP-2 is important for bone regeneration and is a known mediator of vascular calcification, its role in the regulation of atherosclerotic lesions remains uncertain. BMP-2 exerts proinflammatory, proatherogenic effects and can cause oxidative stress in endothelial cells promoting endothelial cell activation [ 37 ]. The current study demonstrates that plasma levels of BMP-2 are significantly higher in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…After 24 h of incubation, the cells that migrated to the lower surface of the filter were fixed by methanol and stained by 1% crystal violet. The number of stained cells from at least 4 fields for each well was counted using a microscope 55 .…”
Section: Methodsmentioning
confidence: 99%